A nano titanium-polyurethane modified epoxy resin anticorrosive coating, a preparation method and application thereof
Patent Information
- Application Number
- CN202510502142.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-21
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-04-21
AI Technical Summary
[0010]有鉴于此,针对现有技术中存在的问题,本发明的目的在于提供一种纳米钛-聚氨酯改性环氧树脂防腐涂层及其制备方法和应用,有效解决了传统环氧防腐蚀涂层固化后韧性差脆性较大,快速固化时内部产生各种缺陷以及功能填料在涂层中分散性较差等问题
[0040] 1. This invention synthesizes a polyurethane-modified epoxy resin with excellent mechanical strength and flexibility as a coating material, which can effectively cope with marine water pressure and deep-sea alternating pressure, and improve the service life of the coating.
Smart Images

Figure CN120209675B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of anti-corrosion coating technology, specifically to a nano-titanium-polyurethane modified epoxy resin anti-corrosion coating, its preparation method, and its application. Background Technology
[0002] Ballast tanks, as vital compartments in marine vessels, often face harsh and complex environments during use. High humidity, high pressure in deep water, and frequent changes in seawater pressure can all cause corrosion and structural damage to equipment, leading to property loss and safety hazards. Applying anti-corrosion coatings is an effective protective measure to extend the service life of ship ballast tanks. Developing long-lasting anti-corrosion coatings for the complex and harsh marine environment is an urgent problem to be solved.
[0003] Epoxy resin-based coatings are among the most widely used coatings in the marine corrosion protection field. The epoxy resin molecule contains polar functional groups such as hydroxyl groups and ether bonds, resulting in excellent adhesion to substrates. Simultaneously, the benzene rings in the molecular chain provide the coating with good rigidity, hardness, and chemical stability. Coatings prepared from epoxy resin with various functional fillers and additives can be used for corrosion protection in different applications, and they also possess advantages such as scalability to production and ease of application. Today, epoxy resin-based coatings are widely used in the corrosion protection of marine vessels and other equipment.
[0004] Question 1: The epoxy resin coating is quite brittle after curing.
[0005] After curing, epoxy resin coatings have good mechanical strength, but poor toughness. Long-term alternating seawater pressure can cause cracks and defects on the surface or inside of the epoxy coating, reducing the protective effect and service life of the coating.
[0006] Question 2: Various defects can occur inside the epoxy resin coating during the curing process.
[0007] Currently, to save construction time and costs, fast-curing, surface-drying anti-corrosion coatings for marine equipment are often favored. However, during the curing process, due to the rapid cross-linking reaction between the resin and the hardener, the coating's interior does not have time to level and fill before the solvent evaporates in large quantities, creating pores. Simultaneously, the internal stress generated by the rapid cross-linking reaction cannot be effectively released, resulting in micro-cracks within the coating. Therefore, traditional fast-drying coatings typically contain defects such as pores and micro-cracks. During use, seawater rich in various corrosive media can penetrate into the substrate through the coating's pores, and alternating pressure can create stress concentrations at the micro-cracks, ultimately damaging the coating and causing its failure, thus failing to provide long-term protection for the metal substrate.
[0008] Question 3: Nanofunctional fillers have high preparation costs and poor dispersibility in coatings.
[0009] Nanomaterials possess a large specific surface area and small size, generally exhibiting superior physicochemical properties compared to traditional materials. As functional fillers, they can not only improve the conventional properties of coatings but also impart other special functions. However, the application of nanofillers in the field of anti-corrosion coatings still faces challenges. First, compared to traditional functional fillers, the preparation of nanofunctional fillers is limited by technological processes, resulting in small-scale production and higher costs. Second, nanomaterials have high surface energy and exhibit interaction forces, making nanoparticles or sheets prone to agglomeration. This leads to poor dispersibility in polyurethane-modified epoxy resins, causing various defects within the coating during curing and reducing the service life of the anti-corrosion coating. Therefore, reducing the production cost of nanofunctional fillers, expanding production scale, and solving the dispersibility problem in coatings are pressing challenges that need to be addressed in the research of anti-corrosion coatings. Summary of the Invention
[0010] In view of this, and in view of the problems existing in the prior art, the purpose of this invention is to provide a nano-titanium-polyurethane modified epoxy resin anti-corrosion coating, its preparation method and application, which effectively solves the problems of poor toughness and brittleness after curing of traditional epoxy anti-corrosion coatings, various internal defects generated during rapid curing, and poor dispersion of functional fillers in the coating.
[0011] The technical solution adopted is as follows:
[0012] The present invention discloses a method for preparing a nano-titanium-polyurethane modified epoxy resin anti-corrosion coating, comprising the following steps:
[0013] S1. Mix polyol and hydroxypropyl-terminated silicone oil and remove water under vacuum, add diisocyanate, and react at 60-80℃ to obtain polyurethane prepolymer;
[0014] S2. Take the polyurethane prepolymer prepared in S1 and blend it with epoxy resin for modification. The reaction temperature is 75-85℃ to obtain polyurethane modified epoxy resin.
[0015] S3. Titanium powder, polyurethane prepolymer prepared in S1 and grinding aid are put into a high-energy ball mill. The titanium powder, polyurethane prepolymer and grinding aid are ground at high speed at room temperature and a rotation speed of 1500-2000 rpm to obtain a black paste-like substance, which is the nano-titanium functional filler.
[0016] S4. First, add the polyurethane-modified epoxy resin, powder filler, dispersant, leveling agent, and defoamer prepared in S2 to the mixed solvent, and stir in a high-speed disperser at 2000-3000 rpm at room temperature to obtain a mixed slurry; then, add the nano-titanium functional filler prepared in S3, and stir in a high-speed disperser at 2000-3000 rpm at room temperature to obtain a nano-titanium-polyurethane-modified epoxy resin coating;
[0017] S5. Add an amine curing agent to the coating and mix and stir. Finally, apply the mixture to the substrate surface and dry to obtain a cured coating.
[0018] Further, in S1, the polyol is one or more of polyethylene glycol, polypropylene glycol, and polybutane glycol; and / or, the diisocyanate is one or more of isophorone diisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate; and / or, the molecular weight range of the hydroxypropyl-terminated silicone oil is 2000-2500.
[0019] Furthermore, in S1, the content of end-capped isocyanate groups in the prepared polyurethane prepolymer is 5%-20% of the mass fraction of the polyurethane prepolymer.
[0020] Furthermore, in S2, the epoxy resin is one or more of E20, E44, E51, and F44.
[0021] Furthermore, in S2, the mass ratio of polyurethane prepolymer to epoxy resin is 1:(2-10); the mass ratio of titanium powder to polyurethane prepolymer is 5:(3-6).
[0022] Furthermore, in S3, the grinding aid is one or more of xylene, n-butanol, and acetone, and / or the titanium powder is high-purity industrial titanium powder with a purity ≥99.95%.
[0023] Furthermore, in S3, the high-energy ball mill has a rotation speed of 1500-2000 rpm and a grinding time of 2-6 hours.
[0024] Further, in S4, the powder filler is one or more of talc, fumed silica, titanium dioxide, and graphene; and / or, the mixed solvent is a mixture of polar and nonpolar solvents.
[0025] Further, in S5, the coating is applied to the surface of the substrate and dried in a forced-air drying oven at 50-100℃ for 4-10 hours to obtain a cured coating.
[0026] Furthermore, in S5, the substrate is Q235 carbon steel with surface pretreatment.
[0027] Furthermore, in S5, the thickness of the cured coating is 100±10μm.
[0028] The present invention provides a nano-titanium-polyurethane modified epoxy resin anti-corrosion coating, which is prepared by the preparation method described in any of the above schemes.
[0029] The application of the nano-titanium-polyurethane modified epoxy resin anti-corrosion coating described above in the surface protection of ballast tanks of marine vessels.
[0030] In the above technical solutions:
[0031] 1. Before synthesizing polyurethane prepolymer, the polyol needs to be dehydrated under vacuum to ensure that the hydroxyl groups that react with the isocyanate groups all come from the polyol.
[0032] 2. Synthesize nano-titanium functional fillers. The high-energy ball mill has a rotation speed of 1500-2000 rpm and a preferred grinding time of 2-6 hours. This ensures that the grinding balls can fully contact and compress with the titanium powder, polyurethane prepolymer, and grinding aid. The mechanical energy generated breaks down and pulverizes the titanium particles, making their particle size nanoscale, and allowing the polyurethane prepolymer to fully coat the surface of the nano-titanium particles.
[0033] 3. When preparing the coating, it is preferable to use a mixture of polar and non-polar solvents to ensure uniform mixing of the polyurethane-modified epoxy resin and the functional filler. Polar solvents may include, for example, one or more of ethyl acetate, n-butanol, and cyclohexanone, while non-polar solvents may include, for example, one or more of toluene and xylene.
[0034] 4. The preferred curing conditions for the coating are drying in a 50-100℃ forced-air drying oven for 4-10 hours. The resin cross-linking and curing reaction rate is moderate with the solvent evaporation rate inside the coating, allowing sufficient time for the coating to level during curing and reducing internal defects after complete curing.
[0035] Features of this invention:
[0036] Feature 1: The polyurethane-modified epoxy resin used as the coating solves the problem of high brittleness after curing of traditional epoxy resin coatings. The polyurethane molecular chain contains both "soft segments" (flexible polyol segments) and "hard segments" (isocyanate segments with a certain degree of rigidity). The polyurethane resin polymerized from these two segments exhibits good flexibility after curing. By modifying the epoxy resin with isocyanate-terminated polyurethane prepolymers, a resin system with excellent mechanical properties can be obtained. The reaction between the isocyanate groups in the polyurethane prepolymer and the hydroxyl groups in the epoxy resin molecular chain forms chemical crosslinks, resulting in the polyurethane-modified epoxy resin. By introducing polyurethane segments, the high brittleness of cured epoxy coatings can be improved without affecting the barrier properties of the coating, enhancing the flexibility of the polyurethane-modified epoxy resin and ensuring the coating remains stable under long-term resistance to alternating seawater pressure.
[0037] Feature 2: The nano-titanium functional filler prepared by high-energy ball milling exhibits excellent dispersibility in polyurethane-modified epoxy resin. Raw titanium powder, polyurethane prepolymer, and grinding aid are fed into a high-energy ball mill. The balls collide with the raw materials as they roll, causing the titanium powder to break down due to impact, reducing the particle size to the nanoscale and significantly increasing its surface energy. Simultaneously, the high energy generated by the collisions between the balls allows the polyurethane prepolymer molecules to coat the metal particles, thus obtaining the nano-titanium functional filler. When this filler is thoroughly mixed with polyurethane-modified epoxy resin, the coating of titanium particles by the polyurethane prepolymer molecules effectively reduces the surface energy and interactions of the nanoparticles, hindering agglomeration and improving dispersibility in the polyurethane-modified epoxy resin. This solves the problem of poor dispersibility of nano-functional fillers in polyurethane-modified epoxy resin and slows down sedimentation, ensuring the quality of the coating during long-term storage.
[0038] Feature 3: The addition of nano-titanium functional fillers can effectively reduce internal defects generated during coating curing and improve the long-term corrosion resistance, alternating stress resistance, and service life of the coating. When nano-titanium functional fillers are uniformly dispersed in the coating, fewer micropores and cracks are generated during the rapid curing process, thereby reducing the channels for corrosive media to penetrate and diffuse into the coating. Furthermore, due to the chemical stability and strong corrosion resistance of titanium, it can effectively block corrosive media. Simultaneously, as a reinforcing phase material in the coating, the uniform dispersion of nano-titanium in the curing system can effectively enhance the mechanical strength of the coating and improve its resistance to alternating seawater pressure.
[0039] Therefore, the beneficial effects of the present invention are as follows:
[0040] 1. This invention synthesizes a polyurethane-modified epoxy resin with excellent mechanical strength and flexibility as a coating material, which can effectively cope with marine water pressure and deep-sea alternating pressure, and improve the service life of the coating.
[0041] 2. This invention utilizes high-energy ball milling to prepare nano-titanium with excellent dispersibility in the polyurethane-modified epoxy resin as a functional filler, which provides effective barrier protection for the coating while reducing internal defects in the coating.
[0042] 3. This invention utilizes the excellent mechanical properties of polyurethane-modified epoxy resin and the synergistic protective effect of nano-titanium filler's good dispersion barrier and mechanical reinforcement to prepare a corrosion-resistant coating for ship ballast tanks with excellent comprehensive performance that can provide long-term corrosion resistance and seawater alternating pressure protection for metal substrates.
[0043] 4. The nano-titanium functional filler prepared by the high-energy ball milling method of this invention has low cost and great industrialization potential. This nano-titanium functional filler has good compatibility with polyurethane-modified epoxy resin. The resulting nano-composite modified epoxy coating, after curing, has fewer internal defects and is denser than traditional composite modified epoxy coatings, exhibiting strong corrosion resistance. Even after prolonged immersion in corrosive solutions, it maintains high adhesion to the metal substrate. Furthermore, due to the uniform distribution of the nano-titanium functional filler within the coating, the coating possesses good toughness and impact resistance. Attached Figure Description
[0044] Figure 1 Infrared spectra of polyurethane prepolymer (PU), nano-titanium (PTiN), and raw material titanium powder (Ti).
[0045] Figure 2 Transmission electron microscopy image of nano-titanium functional filler (PTiN).
[0046] Figure 3 The graph shows the water absorption rate of the coating after 240 hours.
[0047] Figure 4 The electrochemical impedance spectroscopy spectrum is shown after the coating has been immersed for 360 hours.
[0048] Figure 5 The coating resistance R is fitted to the electrochemical AC impedance test data after the coating is immersed for 360 hours. c Bar chart. Detailed Implementation
[0049] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.
[0050] Example 1
[0051] This embodiment describes a method for preparing a nano-titanium-polyurethane modified epoxy resin anti-corrosion coating, comprising the following steps:
[0052] Step 1: Synthesis of polyurethane prepolymer (PU): 1200g of polypropylene glycol 3000, 400g of polybutane glycol 1000, and 240g of hydroxypropyl-terminated silicone oil 2000 were mixed and dehydrated under vacuum for 1 hour. 1100g of 4,4'-diphenylmethane diisocyanate was added, and the mixture was reacted at 80°C for 3 hours to obtain a polyurethane prepolymer with a terminal isocyanate group mass fraction of 10%.
[0053] Step 2: Take 20g of the polyurethane prepolymer PU synthesized in Step 1 and 200g of E44 type epoxy resin for blending modification, and the reaction temperature is 80℃.
[0054] Step 3: Synthesis of nano-titanium functional filler: 500g of high-purity industrial titanium powder (purity ≥99.95%), 600g of the polyurethane prepolymer prepared in the above experiment, and grinding aid were put into a high-efficiency ball mill. The titanium powder, polyurethane prepolymer, and grinding aid were ground at high speed for 4 hours at room temperature and a rotation speed of 1600rpm to obtain a black paste-like substance, which is the nano-titanium functional filler (PTiN).
[0055] Step 4: First, take 130g of polyurethane modified epoxy resin, 11g of talc powder, 1.8g of R972 powder, and 0.1% by mass of dispersant, leveling agent, and defoamer of polyurethane modified epoxy resin. Add them to a mixed solvent of 30g xylene and 10g n-butanol, and place them in a high-speed disperser. Stir at 3000rpm at room temperature for 1 hour to obtain a mixed slurry, thus preparing a polyurethane modified epoxy composite coating.
[0056] Step 5: Add 20% by mass of T31 type curing agent to the coating and mix thoroughly. Apply the cured system to the surface of Q235 carbon steel with dimensions of 60mm×30mm×3mm after surface sandblasting, and place it in an 80℃ forced-air drying oven for 4 hours to obtain a cured coating with a thickness of 100±10μm.
[0057] Figure 1 Infrared spectra of polyurethane prepolymer (PU), nano-titanium (PTiN), and raw material titanium powder (Ti).
[0058] Among them, 1093 cm⁻¹ in the infrared spectrum of PU -1 The characteristic peak corresponds to the Si-O-Si stretching vibration absorption peak of organosilicon, at 1602 cm⁻¹. -1 1527cm -1 1457cm -1 The characteristic peak corresponds to the absorption peak of the aromatic ring skeleton, 810 cm⁻¹ -1 The characteristic peak at 2270 cm⁻¹ corresponds to the stretching vibration peak of organosilicon Si-C. -1 The antisymmetric stretching absorption peak corresponding to the -N=C=O end caps of the molecular chain proves that the PU synthesis was successful. The corresponding group also appeared in the infrared spectrum of PTiN, indicating that the high-energy ball milling technology enabled the PU (polyurethane prepolymer) to be successfully coated on the surface of titanium particles. The disappearance of the -N=C=O absorption peak is because the active group undergoes chemical cross-linking with the surface titanium atoms during the ball milling process.
[0059] Figure 2This is a transmission electron microscope (TEM) image of PTiN. It shows that the raw material Ti was pulverized to nanoscale particle size using high-energy ball milling, and the morphology of the nano-titanium functional filler is that of relatively thin nanosheets.
[0060] Example 2
[0061] This embodiment is basically the same as embodiment 1, except that in step 2, the mass of polyurethane prepolymer PU is 40g.
[0062] Example 3
[0063] This embodiment is basically the same as embodiment 2, except that: in step 4, an additional 10% of nano-titanium functional filler of polyurethane modified epoxy resin needs to be added and placed in a high-speed disperser and stirred at room temperature at 2400 rpm for 3 hours to obtain nano-titanium-polyurethane modified epoxy coating.
[0064] Example 4
[0065] This embodiment is basically the same as embodiment 2, except that: in step 4, an additional 12% of nano-titanium functional filler with polyurethane modified epoxy resin is added and stirred in a high-speed disperser at 2500 rpm at room temperature for 3 hours to obtain nano-titanium-polyurethane modified epoxy coating.
[0066] Example 5
[0067] This embodiment is basically the same as embodiment 2, except that: in step 4, an additional 15% of nano-titanium functional filler with polyurethane modified epoxy resin is added and stirred in a high-speed disperser at 2400 rpm at room temperature for 3 hours to obtain nano-titanium-polyurethane modified epoxy coating.
[0068] Comparative Example 1
[0069] E44 epoxy resin and T31 curing agent were mixed and stirred evenly. The cured system was then applied to the surface of Q235 carbon steel with dimensions of 60mm×30mm×3mm after surface sandblasting. The cured coating was then placed in an 80℃ forced-air drying oven for 4 hours to obtain a cured coating with a thickness of 100±10μm.
[0070] Test Result Analysis
[0071] 1. Coating impact and bending tests
[0072] The standard for testing the impact resistance of the coatings in all examples and comparative examples is GB / T1 732—2020, and the testing instrument is the QCJ type paint film impact tester. The standard for testing the toughness of the coatings is GB / T1731-2020, and the testing instrument is the QTX type paint film elasticity tester.
[0073] The results of the coating toughness and impact resistance tests are shown in Table 1. Compared with Comparative Example 1 (epoxy resin cured coating), Examples 1 and 2 show that the toughness and impact resistance of the polyurethane modified epoxy resin coating are significantly improved.
[0074] The test results of Examples 3 and 4 show that adding an appropriate amount of nano-titanium polymer functional filler will not affect the toughness and impact resistance of the polyurethane modified epoxy resin coating.
[0075] Table 1. Results of impact and bending tests on the coating.
[0076]
[0077]
[0078] 2. Pull-out adhesion test
[0079] All examples and comparative examples of coating adhesion testing were conducted in accordance with GB / T 5210-2006, and the testing instrument was the PosiTest ATA-B pull-out adhesion tester.
[0080] The results of the coating pull-out adhesion test are shown in Table 2. Comparing Examples 1 and 2 with Comparative Example 1, it can be seen that the polyurethane-modified epoxy resin coating maintains the excellent substrate adhesion of the epoxy resin.
[0081] The test results of Examples 3, 4 and 5 show that adding an appropriate amount of nano-titanium polymer functional filler does not affect the adhesion of the polyurethane modified epoxy resin coating.
[0082] Table 2 Results of Coating Pull-out Adhesion Test
[0083]
[0084] 3. Coating water absorption rate
[0085] The experimental standard for testing the water absorption rate of the coatings in all examples and comparative examples is HG / T 3344-2012. After the dry weight of the cured sample coating is tested, it is immersed in a 3.5wt% sodium chloride solution. After that, it is taken out at specific time intervals, the surface water is wiped off, and the weight is weighed to calculate the water absorption rate. The test duration is 240h.
[0086] The test results are attached. Figure 3 As shown, all coatings reached water saturation after 24 hours. Comparative Example 1 (epoxy resin cured coating) had the highest saturation water absorption rate. The test results of Example 1 and Example 2 show that the saturation water absorption rate of polyurethane modified epoxy resin coating decreased. This is because the introduction of polyurethane prepolymer molecular chain segments reduced epoxy resin curing defects.
[0087] The test results of Examples 3, 4 and 5 show that introducing an appropriate amount of nano-titanium polymer functional filler can further reduce the water absorption rate of the coating. This is because the functional filler has good dispersion compatibility in polyurethane modified epoxy resin, improves the density of the cured coating, and plays a barrier role in the cured coating, reducing the diffusion rate of water molecules.
[0088] 4. Electrochemical testing
[0089] The corrosion resistance of the coatings in all examples and comparative examples was tested using electrochemical impedance spectroscopy. The testing platform was a Metrohm PGSTST302N electrochemical workstation. A three-electrode system was selected, with the coated carbon steel sheet as the working electrode (test area radius 1 cm), a saturated calomel electrode as the reference electrode, a platinum sheet electrode as the counter electrode, and a 3.5 wt% sodium chloride solution as the electrolyte. The test frequency range was 10 Hz. 5 -10 -2 The Hz, sinusoidal signal amplitude of 10mV, all examples and comparative examples of coatings were immersed in 3.5wt% sodium chloride solution for 360h and then subjected to electrochemical impedance testing. The test results were fitted using ZView2 software.
[0090] The Bode plot of the electrochemical impedance spectroscopy is attached. Figure 4 As shown in the Bode plot, the low-frequency impedance modulus |Z| 0.01Hz The size directly reflects the corrosion resistance of the coating. After immersion in a 3.5wt% sodium chloride solution for 360 hours, the low-frequency impedance modulus |Z| of the coating in Comparative Example 1 was [not specified]. 0.01Hz At the very least, the test results of Examples 1 and 2 show that the long-term corrosion resistance of the polyurethane-modified epoxy resin coating is significantly improved compared to the epoxy coating. This is because the introduction of polyurethane prepolymer molecular chain segments reduces the curing defects of the epoxy resin and enhances its barrier properties against corrosive media.
[0091] The test results of Examples 3, 4, and 5 show that introducing an appropriate amount of nano-titanium polymer functional filler can further enhance the corrosion resistance of the coating. This is because the functional filler has good dispersion compatibility in polyurethane-modified epoxy resin, which improves the density of the cured coating. The titanium nanoparticles with good chemical stability can effectively block the diffusion of corrosive media to the coating-metal substrate interface, thus improving the long-term corrosion resistance of the coating.
[0092] Electrochemical impedance data were fitted to obtain the coating resistance values R of the examples and comparative examples. c As attached Figure 5 As shown. The coating resistance R in Example 4 is... c It has the highest corrosion resistance.
[0093] The above are merely preferred embodiments of the present invention and do not constitute any limitation on the present invention. Although the present invention has been described through the above embodiments, any adjustments, equivalent modifications, and simple improvements made by those skilled in the art without departing from the spirit, principles, and technical requirements of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a nano-titanium-polyurethane modified epoxy resin anti-corrosion coating, characterized in that, Includes the following steps: S1. Mix polyol and hydroxypropyl-terminated silicone oil and remove water under vacuum, add diisocyanate, and react at 60-80℃ to obtain polyurethane prepolymer; S2. Take the polyurethane prepolymer prepared in S1 and blend it with epoxy resin for modification. The reaction temperature is 75-85℃ to obtain polyurethane modified epoxy resin. S3. Titanium powder, polyurethane prepolymer prepared in S1 and grinding aid are put into a high-energy ball mill. The titanium powder, polyurethane prepolymer and grinding aid are ground at high speed at room temperature and a rotation speed of 1500-2000 rpm to obtain a black paste-like substance, which is the nano-titanium functional filler. S4. First, add the polyurethane-modified epoxy resin, powder filler, dispersant, leveling agent, and defoamer prepared in S2 to the mixed solvent, and stir in a high-speed disperser at 2000-3000 rpm at room temperature to obtain a mixed slurry; then, add the nano-titanium functional filler prepared in S3, and stir in a high-speed disperser at 2000-3000 rpm at room temperature to obtain a nano-titanium-polyurethane-modified epoxy resin coating; S5. Add an amine curing agent to the coating and mix and stir. Finally, apply the mixture to the substrate surface and dry to obtain a cured coating.
2. The method for preparing the nano-titanium-polyurethane modified epoxy resin anti-corrosion coating according to claim 1, characterized in that, In S1, the polyol is one or more of polyethylene glycol, polypropylene glycol, and polybutane glycol; and / or, the diisocyanate is one or more of isophorone diisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate; and / or, the molecular weight range of the hydroxypropyl-terminated silicone oil is 2000-2500.
3. The method for preparing the nano-titanium-polyurethane modified epoxy resin anti-corrosion coating according to claim 1, characterized in that, In S1, the content of end-capped isocyanate groups in the prepared polyurethane prepolymer is 5%-20% of the mass fraction of the polyurethane prepolymer.
4. The method for preparing the nano-titanium-polyurethane modified epoxy resin anti-corrosion coating according to claim 1, characterized in that, In S2, the epoxy resin is one or more of E20, E44, E51, and F44.
5. The method for preparing the nano-titanium-polyurethane modified epoxy resin anti-corrosion coating according to claim 1, characterized in that, In S2, the mass ratio of polyurethane prepolymer to epoxy resin is 1:(2-10); in S3, the mass ratio of titanium powder to polyurethane prepolymer is 5:(3-6).
6. The method for preparing the nano-titanium-polyurethane modified epoxy resin anti-corrosion coating according to claim 1, characterized in that, In S3, the grinding aid is one or more of xylene, n-butanol, and acetone; and / or, the titanium powder is high-purity industrial titanium powder with a purity ≥ 99.95%.
7. The method for preparing the nano-titanium-polyurethane modified epoxy resin anti-corrosion coating according to claim 1, characterized in that, In S4, the powder filler is one or more of talc, fumed silica, titanium dioxide, and graphene; and / or, the mixed solvent is a mixture of polar and nonpolar solvents.
8. The method for preparing the nano-titanium-polyurethane modified epoxy resin anti-corrosion coating according to claim 1, characterized in that, In S5, the coating is applied to the surface of the substrate and dried in a 50-100℃ forced-air drying oven for 4-10 hours to obtain a cured coating.
9. A nano-titanium-polyurethane modified epoxy resin anti-corrosion coating, characterized in that, It is prepared by the preparation method described in any one of claims 1-8.
10. The application of the nano-titanium-polyurethane modified epoxy resin anti-corrosion coating of claim 9 in the surface protection of ballast tanks of marine vessels.
Citation Information
Patent Citations
Polyurethane modified epoxy resin anticorrosion nanometer coating
CN103980797A
High-temperature-resistant and wear-resistant insulating thin spraying coating and preparation process thereof
CN118256143A